Orthodontic treatment in disabled patients. Considerations in this regard - Gretel Rivas Pérez; Ivette Álvarez Mora; Amarelys Morera Pérez; Clotilde de la Caridad Mora Pérez; Yohana Rachel Martínez Román; Thalía Nancy Álvarez Mur (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
Orthodontic care for people with special needs is challenging. The high incidence of malocclusions in these patients threatens their quality of life by generating functional problems in chewing, swallowing and breathing. A bibliographic review was carried out with the objective of describing orthodontic treatment in disabled patients and offering considerations in this regard. It was concluded that malocclusions have a high incidence in disabled patients; the most frequent, generally, are related to the syndrome or condition of these. Orthodontic treatment for these patients must be supported by parents and / or caregivers. Its management will vary according to the disorder it presents; it can be general anesthesia, in the form of drops or intravenous. The goal of treatment must be modified, from trying to pursue orthodontic perfection to seeking a result that is aesthetically and functionally acceptable. For patients with special needs, adherence to and modification of the treatment plan, as necessary, will be the most important for a successful outcome. Disability should not eliminate the possibility of orthodontics as a treatment option.